Samba no pé from Rio:: clues for an ethnographic historiography - Amaral, Fabiana Pereira (Associação Nacional de Pesquisadores em Dança - ANDA, 2024)
Faced with recent decolonial efforts by researchers from the global south, in this essay I try to reflect on the possibility of a historiography of dance based on a very particular manifestation in Rio de Janeiro: the urban samba no pé from Rio de Janeiro. To do this, I propose an approach of exusiac anthropophagy, starting from the body as a document and with a comparative methodology that opens up to various crossroads of knowledge.